Effect of Growth Regulators, Chitosan, and Silver Nanoparticles on Callus Induction and Stimulating the Myricetin Production in Moringa (Moringa Oleifera Lam.) Tree (Texas Journal of Agriculture and Biological Sciences, 2022)
The study was carried out in the laboratory of Fadak Company for Tissue Culture in Abi Al-Khassib district, and the Laboratories of the College of Pharmacy, University of Basrah, Iraq. The nodule stem segments were used as explants that were taken from five-year-old Moringa trees. These explants were cultured on an MS medium supplemented with benzyl adenine at different concentrations (1, 2, 3, and 4 mg L-1 ) for callus induction. The 50 mg weight of induced callus was cultured on MS medium supplemented with different concentrations of chitosan (0, 5, and 10 mg L-1 ) and silver nanoparticles (0, 10, 20, and 30 mg L-1 ) for stimulating the myricetin production. The treatment of 4 mg L-1 benzyl adenine showed significant superiority in the percentage of explant response to callus induction compared to the other treatments, which amounted to 66.0%. But the treatment of 1 mg L-1 benzyl adenine was recorded the lowest response of explants to callus induction, which amounted to 13.77%. The results also showed that the treatment of 5 mg L -1 chitosan was significantly superior in the content of callus of the myricetin compound compared to other treatments, which amounted to 79.572 moles L-1 . The treatment of 10 mg L-1 silver nanoparticles, which recorded the callus content of myricetin compound, amounted to 26.387 moles L-1 . The leaves of Moringa trees recorded 4.714 moles L-1 myricetin compound. While the treatment of silver nanoparticles at 30 mg L-1 recorded the lowest callus content of myricetin, which was 0.668 moles L-1 .